POTENSI LIMBAH CAIR TEH HIJAU SEBAGAI BAHAN PUPUK ORGANIK CAIR DAN PENGARUHNYA TERHADAP PERTUMBUHAN BIBIT TEH - Muningsih, Retno; Ciptadi, Gunawan (Jenderal Soedirman University, 2017)
Tujuan penelitian ini untuk mengetahui kandungan unsur hara limbah cair hasil dari pengolahan teh hijaudan fermentasi limbah cair teh hijau yang digunakan sebagai bahan pupuk organik. Hasil analisa fermentasi limbahcair menunjukkan kandungan C-organik tinggi dan kandungan hara makro serta mikro yang rendah (C-organik5,7; N 0,24%; P 0,06%; K 0,69%, Cu 1,63 ppm dan Zn 3,33 ppm). Pemanfaatan limbah cair teh hijau sebanyak 1liter dengan penambahan starter (EM-4) sebanyak 10 ml belum menunjukkan pengaruh terhadap persentase bibittumbuh dan pertumbuhan bibit, yaitu tinggi tanaman, jumlah dan kehijauan daun bibit teh.Kata kunci: limbah cair teh, pupuk organic, bibit tehABSTRACTThe purpose of this study to determine the nutrient content of liquid waste from the processing of green teaand green tea fermentation liquid waste used as organic fertilizer. The benefits to be obtained is to provideinformation on the nutrient content of the liquid waste from the processing of green tea and green tea fermentationliquid waste used as organic fertilizer. Results of analysis of liquid waste showed high content of organic C (5,7%)and nutrient content of macro and micro low i.e N 0.24%, P 0.06%, K 0.69%, Cu 1.63 ppm and Zn 3.33 ppm.Liquid waste green tea as much as 1 liter with the addition of starter (EM-4) as much as 10 ml has not shown theeffect on the percentage of seedlings and growth of seedlings i.e plant height, number of leaves and greenery.Key words: liquid waste of tea, organic matter, tea seedling